2015
DOI: 10.1002/asi.23303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of domain on measures of semantic relatedness

Abstract: Measures of semantic relatedness have been used in a variety of applications in information retrieval and language technology, such as measuring document similarity and cohesion of text. Definitions of such measures have ranged from using distance‐based calculations over WordNet or other taxonomies to statistical distributional metrics over document collections such as Wikipedia or the Web. Existing measures do not explicitly consider the domain associations of terms when calculating relatedness: This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…On the other hand, if the user explicitly indicates the domain of the query, this not only eliminates the query-classification step, but should also help to reduce any ambiguity that might be present. In recent work, Macias-Galindo et al [2015] have confirmed that the domain of interest is important when quantifying the semantically relatedness between words. Even though their experiments were not directly related to QE, their findings are expected to be applicable when estimating the semantic relation between the query and candidate expansion terms.…”
Section: Medical Recordsmentioning
confidence: 83%
“…On the other hand, if the user explicitly indicates the domain of the query, this not only eliminates the query-classification step, but should also help to reduce any ambiguity that might be present. In recent work, Macias-Galindo et al [2015] have confirmed that the domain of interest is important when quantifying the semantically relatedness between words. Even though their experiments were not directly related to QE, their findings are expected to be applicable when estimating the semantic relation between the query and candidate expansion terms.…”
Section: Medical Recordsmentioning
confidence: 83%